The Effect Of Transformational Leadership Style, Transactional Leadership And Charismatic Leadership On Organizational Citizenship Behavior (Ocb) with Working Culture as an Intervening Variable - Andika Prasetya Nugraha (IAIC Publishing, 2021)
This study aims to determine the effect of transformational leadership style and transactional leadership style on extra-role behavior or often called Organizational Citizenship Behavior (OCB) in the Regional Government Secretariat of Karimun Regency. Extra role behavior performed by civil servants cannot be separated from the patterns and abilities of each employee's character. This character can be called the work culture of each of these employees. Are the two leadership styles namely the Transformational leadership style, Transactional leadership and Charismatic leadership can increase extra-role behavior or often called Organizational Citizenship Behavior (OCB) where work culture is an intervening variable. This research was conducted at the Secretariat of the Regional Government of Karimun Regency, Riau Islands. The population in this study was 50 employees. By using the census method where the number of research samples will be taken as a whole from members of the population. Data were analyzed using Structural Equation Modeling (SEM).